Review: Non-Invasive Therapy for Diabetes Mellitus Using Solid Lipid Nanoparticle - KAMBLE, S. S.; GAMBHIRE, M. S.; GUJAR, K. N.; AFSHINFAR, M. H. (Asian Journal of Pharmaceutical Research and Development, 2015)
Oral delivery of Insulin as a non-invasive therapy for Diabetes Mellitus is still a challenge for the drug delivery technology, as it is degraded due to the presence of enzymes in the acidic environment of stomach and also its absorption through the gastrointestinal mucosa is doubtful.Advancements in nanotechnology have brought the scientist ever closer to this goal.The current review focuses on the various barriers existing in the route of oral insulin delivery and the strategies undertaken so far to overcome those by nanoparticle as potential vehicles of insulin. The oncoming years shall be interesting in the form of more oral insulin preparations actually becoming available and affordable to those thousands who are awaiting a relief from the stress and distress of daily insulin injections.